Meningkatkan keterampilan guru dalam membuat rencana pelaksanaan pembelajaran tematik melalui workshop - Suwardi Suwardi (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
Students who are in grade one, two, and three elementary schools are in the early age range. At that age, all aspects of intelligence development such as IQ, EQ, and SQ grow and develop in a very extraordinary way and seeing everything as a whole (holistic) is able to understand the relationship between concepts in a simple way. The learning process still depends on concrete objects and experiences directly experienced. The implementation of learning activities in SD grades I - III for each subject is carried out separately, for example Civics 2 hours of lessons, 2 hours of social studies, and 2 hours of Indonesian Language. In the implementation of activities carried out purely in subjects, namely only studying the competency standards and basic competencies related to these subjects. In accordance with the stages of child development as a wholeness (holistic), learning separate subjects will cause less development of children to think holistically and make it difficult for students. Can the workshop improve the skills of teachers in making plans for implementing thematic learning ?; Can the workshop increase teacher activity in making plans for implementing thematic learning? Improve the skills of teachers in making plans for implementing thematic learning workshops; To find out the activities of teachers in making plans for implementing thematic learning, it is carried out by observing teacher activities in workshop activities.